If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7k+36=6(8-k)-4
We move all terms to the left:
-7k+36-(6(8-k)-4)=0
We add all the numbers together, and all the variables
-7k-(6(-1k+8)-4)+36=0
We calculate terms in parentheses: -(6(-1k+8)-4), so:We get rid of parentheses
6(-1k+8)-4
We multiply parentheses
-6k+48-4
We add all the numbers together, and all the variables
-6k+44
Back to the equation:
-(-6k+44)
-7k+6k-44+36=0
We add all the numbers together, and all the variables
-1k-8=0
We move all terms containing k to the left, all other terms to the right
-k=8
k=8/-1
k=-8
| –9−y=y+9 | | 1/3-1/6(x-1)=1/3 | | 6x+21x=3 | | -39+11x=33+13x | | 6=¼x+2 | | -2(4y-5)=-3(2y-4) | | 4/3(2x+1)=12 | | (12x+11)+(9x+3)+(7x+26)=180 | | 13=9+x^2 | | 10p+4=5p-26 | | 16y+-3y+-19y=-18 | | −4p+(−6p)= | | -8(7+2x)=-136 | | 6a-6-2a=12 | | 4n+19=4n+20 | | 11=g–3+ 15 | | 126=5^x+1 | | |2-10|=-3x | | 60=0.1*x | | 15t+3=117 | | −4x+7=11 | | -118=-5(4=7x)=7 | | 6(2n+3)=14n | | 86=2(3-5x) | | -17y—14y=9 | | -9x-92=4x+93 | | 2j-6=10+4j | | -25=-4(8+4a)+7(1-5a) | | 7x-4+3=8× | | Y=(x-5)2-9 | | -2(4x-8)+4=-60 | | 1+5(7v+6)=206 |